Perjuangan Kesetaraan dalam Novel Fatatu As-Sajair Karya Ratih Kumala (Kajian Kritik Sastra Feminis) - Arsita, Wina; Mardiansyah, Yadi; Ridho, Muhammad Rosyid (UIN Sunan Gunung Dajti Bandung, 2023)
Abstract: This study explains the struggle for gender equality of female figures in several of its parts. The novel Fatatu As-Sajair presents a female characters who has an influence on the development of cigarettes in Indonesia. The representation of female characters in this novel not only places women in an inferior position, but can also be in a superior position. The purpose of this study is to explain the socialist feminism contained in the novel. This study uses a qualitative descriptive analysis method with a type of literary criticism approach, namely feminist literary criticism. The research results from the novel Fatatu As-Sajair show that the novel contains female characters fighting for gender equality by working in the clove cigarette sector.